Verbs in Tatar Advertisements - ZAMALETDINOVA, GULNARA FANDASOVNA; ZAMALETDINOV, RADIF RIFKATOVICH; FAKHRETDINOVA, GULNAZ NURKHAMETOVNA; NEVSKAYA, IRINA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article discusses the functioning of the verb in the Tatar advertising texts. Our study of Tatar advertising texts showed that the verb plays an important role in realizing the pragmatic potential. Future tense assures the consumer’s right decision about a particular product or service. The past tense is used in the narrative of past actions that have a positive result. The imperative mood is used to encourage action possessing different semantic meanings: command, advice, request to perform an action. The conditional mood expressed by lexical and grammatical means and intonation, strengthens the belief about the right choice. RESUMEN El artículo analiza el funcionamiento del verbo en los textos publicitarios tártaros. Nuestro estudio de textos publicitarios tártaros mostró que el verbo juega un papel importante en la realización del potencial pragmático. El tiempo futuro asegura la decisión correcta del consumidor sobre un producto o servicio en particular. El tiempo pasado se usa en la narración de acciones pasadas que tienen un resultado positivo. El estado de ánimo imperativo se utiliza para alentar la acción que posee diferentes significados semánticos: comando, consejo, solicitud para realizar una acción. El estado de ánimo condicional expresado por medios léxicos y gramaticales y entonación, fortalece la creencia sobre la elección correcta.